2018
DOI: 10.1111/tbed.12799
|View full text |Cite
|
Sign up to set email alerts
|

FaecalEscherichia colias biological indicator of spatial interaction between domestic pigs and wild boar (Sus scrofa) in Corsica

Abstract: SummaryOn the Mediterranean island of Corsica, cohabitation between sympatric domestic pigs and Eurasian wild boar (Sus scrofa) is common and widespread and can facilitate the maintenance and dissemination of several pathogens detrimental for the pig industry or human health. In this study, we monitored a population of free-ranging domestic pigs reared in extensive conditions within a 800-ha property located in Central Corsica which was frequently visited by a sympatric population of wild boar between 2013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In the case of HEV, several recent studies have shown that several strains are shared between pigs, wild boars, pork products, and humans ( 16 , 51 ). Such approaches can be relevant to address the question of environmental contamination ( 52 ). Concerning ADV, a major issue is the technical difficulty to collect samples containing the virus, as Aujeszky’s disease symptoms are difficult to notice in free ranging farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HEV, several recent studies have shown that several strains are shared between pigs, wild boars, pork products, and humans ( 16 , 51 ). Such approaches can be relevant to address the question of environmental contamination ( 52 ). Concerning ADV, a major issue is the technical difficulty to collect samples containing the virus, as Aujeszky’s disease symptoms are difficult to notice in free ranging farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of pig groups in this territory varies; during the winter months, pigs tend to remain close to the farm for supplementary feeding and reproduction, during autumn and early winter (i.e. the chestnut harvesting period), free‐ranging pigs are left in the mountain plains (Barth et al., 2018). In summer, pigs are traditionally kept in often‐unfenced grass pastures and beech forests found at higher altitudes (Jori et al., 2017).…”
Section: Assessmentmentioning
confidence: 99%
“…Dogs living on farms could also contribute to the spread of ESBL- E. coli among agricultural settings because contact with livestock has been associated with an increased probability of ESBL- E. coli fecal carriage in dogs [ 27 , 28 , 29 , 30 ]. However, the circulation of ESBL- E. coli at the livestock and wildlife interface is still poorly understood [ 12 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%